Optimizing Smoking Cessation Counseling in a University Hospital: Results and Pitfalls - de Frel, Daan L.; Janssen, Veronica R.; Meijer, Eline; Atsma, Douwe E. (Frontiers in Health Services, 2022)
Healthcare professionals (HPs) can play a substantial role in smoking cessation counselling (SCC) but in practice often skip this task due to time constraints. This study evaluates the implementation of the rapid Ask-Advise-Connect (AAC) method in a University hospital setting. This mixed methods pre-post interventional study was performed at the Cardiology department of a University hospital and consisted of 1) a quantitative assessment of patient smoking registration and HP connection rates to external SCC from the Electronic Medical Record, 2) semi-structured interviews with 10 HPs to assess their attitudes towards AAC, and 3) a blended intervention aimed to implement AAC. The blended intervention consisted of face-to-face and online AAC psychoeducation for HPs followed-up with motivational messages on their smart pagers over a period of 6 weeks. In total, 48,321 patient registrations and 67 HPs were included. Before AAC implementation, HPs assessed smoking status in 74.0% of patients and connected 9.3% of identified smokers with SCC. Post intervention, these percentages did not increase (73.2%, p=0.20; and 10.9%, p=0.18, respectively). Nonetheless, the vast majority (90%) of HPs feel it is important to discuss patient smoking, and view it as their duty to do so. Main barriers to AAC reported by HPs were forgetfulness and time pressure. This study shows that this AAC intervention does not increase Asking after smoking status or Connection of patients to SCC in a University Hospital. However, HPs hold positive attitudes towards AAC. A better understanding of the mechanisms required for optimizing HPs practice behaviour is needed.